Timing of extreme heat events matters: exposure during parasitism disrupts top-down control - Pardikes, Nicholas A; Revilla, Tomas A; Proudhom, Gregoire; Thierry, Melanie; Lue, Chia-Hua; Hrcek, Jan (Oecologia, 2025)
Due to ongoing climate change, extreme climatic events are expected to increase in magnitude and frequency. While individual species' responses to thermal extremes are widely studied, the impact of extreme heat events on species interactions and the key functions they provide in communities is understudied. As outcomes of species interactions depend on coordinated physiology and development, the consequences of heat exposure are likely impacted by its timing relative to the organisms' life history traits, but to what extent is unclear. In this study, we evaluate how the timing of heat exposure affects interactions among nine tropical Drosophila-parasitoid species combinations using laboratory microcosm experiments. Interactions were most affected when heat exposure coincided with parasitism, leading to decreased parasitism rates. Parasitism rates also dropped when extreme heat occurred after parasitism in one instance. Experiencing heat exposure before parasitism had little effect. Using a simulation model, we determined that the combined effects of parasitism and heat exposure are generally additive, with no evidence of delayed consequences of heat exposure early in development on parasitism outcomes. Furthermore, we found adult host flies and parasitoids more resistant to heat exposure than their larval stages. Thus, whether more frequent extreme heat events disrupt species interactions globally will depend on their exact timing relative to ontogenetic stages and interactions. Heat exposure impacts the two trophic levels differently. Thus, when heat exposure coincides with parasitism, it may diminish the ability of parasitoids to control their hosts, affecting both natural ecosystems and agricultural environments.
Keywords: Climate change; Animals; Drosophila; Climate Change; extrémní horko; zvířata; Host-Parasite Interactions; Extreme Heat; Larva; Host–parasitoid; Tropical ecology; interakce hostitele a parazita; Communities; Ontogeny; klimatické změny; larva